MIMETIC RESISTANCE - Hernández, Teresa Casas (Homo Mimeticus II, 2024)
The mimetic turn is the re-turn of orality. As I will show through attention to details of Plato’s and Aristotle’s mimetic agon, orality is the ontology of mimesis. At the dawn of mimetic studies, the two philosophers recognize that human beings are homo mimeticus, namely, mimetic animals; equally, they tie knowledge, mimesis and human nature as far as the human natural inclination to mimesis is the manifestation of the equally human natural desire for knowledge.¹ In doing so, they discard oral mimesis in favor of abstract mimesis. The mimetic turn entails the recovering of the fundamental aspect of orality in